Gaya Komunikasi Dalam Kepemimpinan Dan Komitmen Guru SMA Negeri Di Jakarta Timur - fitri argarini (Cakrawala - Jurnal Humaniora, 2023)
This study examines leadership communication styles (transformation, transactions) and job satisfaction on teacher commitment in East Jakarta State Senior High Schools. This study used a method with a factorial data collection design by distributing questionnaires to teachers of SMA Negeri in East Jakarta with a total of 60 samples. The results of the study show that there is a difference between teacher commitment and the transformation of the principal. Leadership and organizational commitment exist between teachers. with high job satisfaction and low job satisfaction so that job satisfaction is high when teacher commitment is more positive with the principal's transformational leadership style, where job satisfaction is low when the teacher's organization is more open to the principal based on interaction and influence-based communication style between the principal's leadership communication and teacher commitment organization. So it can be interpreted that the influence of leadership communication style and job satisfaction has a positive effect on organizational commitment. Keywords: Communication style, Transformational, transactional, job satisfaction, organizational commitment